2000
DOI: 10.1192/apt.6.5.362
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment in older people: old principles and new directions

Abstract: Neuropsychological assessment, in the broader sense, is common clinical practice with older adults because of the widespread use of mental status examinations and dementia rating scales. In the more narrow sense, a neuropsychological assessment conducted by a clinical psychologist or clinical neuropsychologist is used less frequently and for more specific purposes. This paper outlines these uses and provides a brief overview of the different types of test that might be used, with a clinical example to illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
2
11
0
Order By: Relevance
“…[30] In this research, the RAVLTs demonstrated the best discrimination validity for dementia, thus confirming their utility in diagnosing the disorder. With the exception of trial I of the RAVLTs, all the RAVLT subtest measures displayed significance at p<0.001.…”
Section: Screening For Dementiasupporting
confidence: 59%
“…[30] In this research, the RAVLTs demonstrated the best discrimination validity for dementia, thus confirming their utility in diagnosing the disorder. With the exception of trial I of the RAVLTs, all the RAVLT subtest measures displayed significance at p<0.001.…”
Section: Screening For Dementiasupporting
confidence: 59%
“…Cognition was assessed by two scales: mini mental state examination (MMSE) (Folstein et al, 1975) and the Kendrick object learning test (KOLT) (Kendrick et al, 1979). The KOLT is a visual memory test and is included in Kendrick assessment scales of cognitive ageing (KASCA) (Morris and Claire Matthews, 2000). KOLT has a maximum total score of 70 and minimum score of 0 (the set of cards presented can be abbreviated to sub-scores of 10, 15, 20 and 25, corresponding to the number of objects visible).…”
Section: Independent Variablesmentioning
confidence: 99%
“…In large cohort studies, declines in measures of delayed recall or accelerated forgetting were the best discriminators between patients with mild and non-dementia 8,20,25,26 . With increasing severity of illness, patients also have a constriction of immediate recall.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, MMSE does not analyze behavioral changes, which are important in Alzheimer's disease (AD) and frontotemporal dementia (FTD) diagnosis 6,7 . Therefore, MMSE may not be sufficient to assess the severity of clinical course of other types of dementia 8 . Considering these MMSE limitations, Dr. David Libon created in 2007 the Philadelphia Brief Assessment of Cognition (PBAC), a neuropsychological screening instrument sensitive to neuropsychological deficits associated with AD and patients with FTD dementia 7 .…”
mentioning
confidence: 99%